Literary and Colloquial Pronunciations of the Peking Mandarin Noted by Joseph Edkins in Romanized Chinese Book - Wong , Ling Yann (2011)
A Progressive Lessons in the Chinese Spoken Language is a romanized Chinese book compiled by Joseph Edkins in the middle of the nineteenth century, this book is provided to foreigners who stayed in China at that time for learning the Peking Mandarin. The characteristics of the pronunciations which reflected in the “Lessons”（《課文》）and the“List of Common Words and Phrases”（《編目表》）in this book have shown differentiated, the former refered to the classical rhyming book namely as Wufang Yuanyin （《五方元音》）to form the literary pronunciation of Mandarin, Joseph Edkins believed that this sound system which has been noted in this rhyming book is used to form the literary pronunciation of the Peking Mandarin, and it is the standard Mandarin Orthography；however the latter reflected the colloquial pronunciation of the Peking Mandarin which spoken by the local people, this actual sound is originated from the Peking dialect. The basic sound systems which have been formed in the “Lessons”and the“List of Common Words and Phrases”are differentiatied, thus both sound systems have shown the different characteristics in consonants, rhymes and tones. This study also found that the sound systems of this Chinese book are not originated from the Nanking Mandarin, but its based on the written language of the classical rhyming book and the Peking dialect to form the literary and colloquial pronunciation of the Peking Mandarin.